Mortgage-Related Bank Penalties and Systemic Risk among U.S. Banks - Václav Brož; Evžen Kocenda (Center for Economic Studies and ifo Institute (CESifo), 2021)
We analyze link between mortgage-related regulatory penalties levied on banks and the level of systemic risk in the U.S. banking industry. We employ a frequency decomposition of volatility spillovers (connectedness) to assess system-wide risk transmission with short-, medium-, and long-term dynamics. We find that after the possibility of a penalty is first announced to the public, long-term systemic risk among banks tends to increase. From the dynamic perspective, bank penalties represent an overlooked risk as they do not increase systemic risk immediately, but the risk accumulates and propagates over the long-term. In this respect, bank penalties resemble still waters that run deep. In contrast, a settlement with regulatory authorities leads to a decrease in the long-term systemic risk. Our analysis is robust with respect to a number of relevant criteria.
Keywords: C14; C58; G14; G21; G28; K41; 330; bank; global financial crisis; mortgage penalty; systemic risk; financial stability